Genetic Diversity In Different Stocks Of Grass Carp (Ctenopharyngodon Idellus) Inferred By Random Amplified Polymorphic Dna (Rapd) Markers In India (Applied Biological Research, 2014)
Four different stocks of grass carp from different geographical locations  viz., Kolkata, Kaikaluru, BRP and Thanjavur representing varied  environmental conditions were collected from Kolkata (West Bengal), Kaikaluru (Andhra Pradesh), Shimoga (Karnataka) and Thanjavur  (Tamilnadu). The stocks were marked using fin cauterization for easy  identification during the growth behaviour studies. Growth behavior  sudies conducted under same environmental and management conditions.  RAPD analysis was performed for different stocks of grass carp. Of the  100 decamer primers screened, seven primers (OPA 1, OPA 18, OPB 11,  OPB 19, OPD 11, OPD 18 and OPE 10) gave consistent and at least two  polymorphic bands. The RAPD analysis showed that Kolkata stock had 2.74 to 14.72% higher polymorphic bands in comparison with other stocks.  The Kolkata stock was found closely related to Kaikaluru stock but distantly related to Thanjavur stock. Growth trials indicated better  performance of Kolkata stock in comparison to other stocks. The r2value  between the % polymorphism and mean body weight attained by different  stocks of grass carp showed that these two parameters were positively  correlated.
Keywords: Genetic diversity; grass carp; polymorphism; random amplified polymorphic DNA (RAPD) markers